Labor market - Lim, Kean Fan (Wiley-Blackwell, 2015)
Labor markets are socially-constructed entities that facilitate the buying and selling of labor power. They are effectively political-geographic institutions, governed predominantly by state regulations that apply within specific territorial boundaries. For this reason, analyses of labor markets have tended to be state-centric. Economic geographers have worked assiduously at transcending state-centrism through showing how the buying and selling of labor power is a gendered, multi-dimensional and often transnational process – it is never about the self-correction of prices by abstract forces of demand and supply.